Burden of ischemic heart disease mortality attributable to physical inactivity in Brazil - Diego Augusto Santos Silva; Deborah Carvalho Malta; Maria de Fatima Marinho de Souza; Mohsen Naghavi (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To analyze if the burden of ischemic heart disease mortality trend attributed to physical inactivity in Brazil differs from the global estimates. METHODS Databases from the Global Burden of Disease Study for Brazil, Brazilian states, and global information were used. We estimated the summary exposure value for physical inactivity, the total number of deaths, and the age-standardized death rates for ischemic heart disease attributed to physical inactivity in the years 1990 and 2015, and the population-attributable fraction. Data were presented according to sex. RESULTS The Brazilian population was found to have a risk of exposure to physical inactivity varying between 70.4% for men and 75.7% for women in the year of 1990. This risk of exposure was similar in 2015. In men, the mortality rate from ischemic heart disease attributed to physical inactivity decreased in 2015 by approximately 24% around the world and 45% in Brazil. For women, this decrease was in 31% around the world and 45% in Brazil. The states of Southern and Southeastern Brazil presented lower mortality rates due to ischemic heart disease attributed to physical inactivity. If physical inactivity were eliminated in Brazil, mortality from ischemic heart disease would be reduced by 15.8% for men and 15.2% for women. CONCLUSIONS Over 25 years, the risk of exposure to physical inactivity in Brazil did not change and was high compared to global estimates. The decrease in ischemic heart disease mortality results from the improvement of health services in Brazil and the control of other risk factors. Approximately 15% of deaths from ischemic heart disease in Brazil could be avoided if people met the recommendations for physical activity.